You are on page 1of 5

# Math 1005 H Fall 2015

Tutorial 6
1. Find the radius and interval of convergence for the power series

X 2n (x − 5)n
.
n=0
n2 + 1

2n
Solution: This is a power series centred at 5 with coefficients cn = n2 +1
. We
use theorem 7.1:

cn
R = lim
n→∞ cn+1

2n ((n + 1)2 + 1)
= lim
n→∞ (n2 + 1)2n+1
1 n2 + 2n + 2
= lim
2 n→∞ n2 + 1
1 1 + n2 + n22
= lim
2 n→∞ 1 + n12
1
= .
2
The radius of convergence is R = 21 . That is, the series converges absolutely for
1
|x − 5| <
2
1 1
− <x−5<
2 2
9 11
<x< .
2 2
To find the interval of convergence, we must test the end points. At x = 92 , the
series is
∞ ∞ n
X 2n ( 92 − 5)n X 2n − 12
2+1
=
n=0
n n=0
n2 + 1

X (−1)n
= ,
n=0
n2 + 1
11
which converges (absolutely). At x = 2
, the series is
∞ ∞ n 1 n
2n ( 11 n

X
2
− 5) X 2 2
2+1
= 2+1
n=0
n n=0
n

X 1
= ,
n=0
n2 +1
9 11

which converges. Thus the interval of convergence is I = ,
2 2
.

X 1
2. Use the geometric series tn = (for |t| < 1) to find the Maclaurin series
n=0
1 − t
of f (x) = tan−1 (x) and determine its radius of convergence.

1
= tan−1 (x) + C. Letting t = −x2 in the geo-
R
Solution: Recall that 1+x2
dx
metric series, we have
∞ ∞
1 X
2 n
X
= (−x ) = (−1)n x2n
1 + x2 n=0 n=0

for | − x2 | < 1, which is the same as |x| < 1. Integrating term by term, we have
Z ∞ Z
1 X
n
dx = (−1) x2n dx,
1 + x2 n=0

and so ∞
−1
X (−1)n 2n+1
tan (x) = x +C
n=0
2n + 1
for |x| < 1. Letting x = 0, we have 0 = tan−1 (0) = 0 + C, so C = 0. The
Maclaurin series for tan−1 (x) is

X (−1)n 2n+1
tan−1 (x) = x
n=0
2n + 1

with radius of convergence R = 1.
2
3. Find the Maclaurin series of f (x) = e−x and determine its radius of conver-
gence.

Solution: Let’s make use of the fact that we know the Maclaurin series for et :

t
X 1 n
e = t
n=0
n!

for all t. Letting t = −x2 , we have
∞ ∞
−x2
X 1 2
X (−1)n 2n
e = (−x )n = x .
n=0
n! n=0
n!

This is valid for all x, so the radius of convergence is ∞.

Note: We could have used the formula for the coefficients of a Maclaurin series
to do this question, but the method given above is much easier. I encourage
Interesting consequence: Integrate this series from 0 to t term by term to get
Z t ∞
t ∞
n
−x 2
X (−1)
2n+1
X (−1)n 2n+1
e dx = x = t .
0 n!(2n + 1)
n=0
n!(2n + 1)
n=0
0
The integral on the left can not be evaluated in terms of “elementary” functions,
but we are still able to find its Maclaurin series. It’s an important integral, which
is used to find probabilities in the normal distribution.
3
4. Write down the first few terms of the Taylor series for f (x) = x 2 about 9.

(n) f (n) (9)
Solution: We have a = 9, and so cn = f n!(a) = n!
. We compute the first
few derivatives of f and evaluate them at 9:
3 3
f (x) = x 2 f (9) = 9 2 = 27
3 1 3 1 9
f 0 (x) = x 2 f 0 (9) = 9 2 =
2 2 2
3 1 3 1 1
f 00 (x) = x− 2 f 00 (9) = 9− 2 =
4 4 4
3 3 3 3 1
f 000 (x) = − x− 2 f 000 (9) = − 9− 2 = −
8 8 72
9 5 9 5 1
f (4) (x) = x− 2 f (4) (9) = 9− 2 = .
16 16 432
Thus
f (9)
c0 = = 27
0!
f 0 (9) 9
c1 = =
1! 2
f 00 (9) 1
c2 = =
2! 8
f 000 (9) 1
c3 = =−
3! 432
(4)
f (9) 1
c4 = = .
4! 10368
3
The first few terms of the Taylor series for f (x) = x 2 centred at 9 are
9 1 1 1
27 + (x − 9) + (x − 9)2 − (x − 9)3 + (x − 9)4 + ...
2 8 432 10368

− ln(1 − 3x)(e2x − 1)
5. Evaluate lim .
x→0 sin(x2 )

Solution: We use the Maclaurin series expansions of − ln(1 − x), ex , and sin(x),
all seen in class. Since
x2 x3
− ln(1 − x) = x + + + ...,
2 3
we have
9x2 27x3
− ln(1 − 3x) = 3x + + + ...
2 3
Since
x2 x3
ex = 1 + x + + + ...,
2! 3!
we have
2x 4x2 8x3
e − 1 = 2x + + + ...
2! 3!
Since
x3 x5
sin(x) = x − + + ...,
3! 5!
we have
x6 x10
sin(x2 ) = x2 − + + ...
3! 5!
Thus
  
9x2 27x3 4x2 8x3
− ln(1 − 3x)(e2x
− 1) 3x + 2
+ 3
+ ... 2x + 2!
+ 3!
+ ...
lim = lim x6 10
x→0 sin(x2 ) x→0 + x5! + ...
x2 − 3!
  
27x2 8x2
x2 3 + 9x2
+ 3
+ ... 2 + 4x
2!
+ 3!
+ ...
= lim 4 8
x2 1 − x3! + x5! + ...

x→0
  
27x2 8x2
3 + 9x
2
+ 3
+ ... 2 + 4x
2!
+ 3!
+ ...
= lim 4 8
x→0 1 − x3! + x5! + ...
(3)(2)
=
1
= 6.

Note that using l’Hôpital’s rule to evaluate this limit would be annoying, as it
would take a few applications and the derivatives would not be pleasant to work
with.

Additional examples if there is extra time

6. Find the coefficient of x9 in the Maclaurin series expansion of (1 − x3 )−3 .
Solution 1 (elegant): We exploit the fact that

1 X
= tn .
1 − t n=0

We differentiate twice:

1 X
= ntn−1
(1 − t)2 n=1

2 X
= n(n − 1)tn−2 .
(1 − t)3 n=2
Letting k = n − 2, we have

1 X (k + 2)(k + 1)
= tk .
(1 − t)3 k=0
2
Letting t = x3 (and replacing k with n), we have

1 X (n + 2)(n + 1) 3n
(1 − x3 )−3 = = x .
(1 − x3 )3 n=0
2
(3+2)(3+1)
Since 3n = 9 for n = 3, the coefficient of x9 is 2
= 10.

f (9) (0)
Solution 2 (sketch): Letting f (x) = (1−x3 )−3 , the coefficient of x9 is c9 = 9!
.
We must differentiate f (x) nine times.
f (x) = (1 − x3 )−3
f 0 (x) = −3(1 − x3 )−4 (−3x2 )
..
.
1814400(2 + 636x3 + 13233x6 + 63140x9 + 92208x12 + 42432x15 + 4862x18 )
f (9) (x) =
(1 − x3 )12
(I used a computer, as nobody wants to do this by hand!). We have f (9) (0) =
1814400(2) = 3628800. Thus
3628800
c9 = = 10.
9!
It should be clear that the first solution is much better than this solution.
7. Find the radius and interval of convergence for the power series

X 32n (x + 3)n
.
n=0
(2n)!
32n
Solution: This is a power series centred at −3 with coefficients cn = (2n)!
. We
use theorem 7.1:

cn
R = lim
n→∞ cn+1

32n (2(n + 1))!
= lim
n→∞ (2n)!(32(n+1) )

32n (2n + 2))!
= lim
n→∞ (2n)!(32n+2 )

1 (2n + 2))!
= lim
9 n→∞ (2n)!
1
= lim (2n + 2)(2n + 1)
9 n→∞
=∞
The radius of convergence is R = ∞. That is, the series converges absolutely
for all x. The interval of convergence is I = (−∞, ∞).